Răspuns :
10-10:{1+3*[(57:15*2):3+20:10]}=
10-10:{1+3*[(57-30):3+20:10]}=
10-10:[1+3*(27:3+20:10)]=
10-10:[1+3*(9+2)]=
10-10:(1+3*11)=
10-10:(1+33)=
10-10:34=?
Este greșită problema aceasta , am încercat să schimb câte un număr dar nu merge , este greșită.
10-10:{1+3*[(57-30):3+20:10]}=
10-10:[1+3*(27:3+20:10)]=
10-10:[1+3*(9+2)]=
10-10:(1+3*11)=
10-10:(1+33)=
10-10:34=?
Este greșită problema aceasta , am încercat să schimb câte un număr dar nu merge , este greșită.
1)60÷4=15
2)15×2=30
3)57-30=27
4)27÷3=9
5)9+21=30
6)30÷10=3
7)3×3=9
8)9+1=10
9)10÷10=1
10)10-1=9
2)15×2=30
3)57-30=27
4)27÷3=9
5)9+21=30
6)30÷10=3
7)3×3=9
8)9+1=10
9)10÷10=1
10)10-1=9